Digital breakthrough: will public administration be smart enough in a digital state and how smart are the elite and citizens - L. A. Vasilenko (Цифровая социология)
The digital society is considered as a superintelligent society of a hybrid type, corresponding to the sixth technological order, in which the transgression of virtual relations into the real socio-cultural world is carried out, the hybrid collective mind is accumulated and intelligently used. The article raises the question – is it possible for subject-subject smart public administration in Russia, whether the subjects of management are smart and qualified enough in the context of digitalization, whether they will be able to effectively use smart technologies and smart services. To do this, the author discusses, first, the problem of what is a smart subject of management and how to measure the degree of smartness. In the discourse of digital society, the measurement of the degree of smartness of the subject of management is based on: the ability of an individual to perform managerial functions and on the possession of digital competencies. Secondly, the issue of assessing the current situation in Russia is investigated, i.e. to what extent digitalization creates conditions for the functioning of smart governance in Russia. The model of a centralized ecosystem of an IT-state of a service nature in Russia is implemented on a single architecture with the inclusion of components of state remote control of the objects of supervision, as well as on the principles of “human independence” and interdepartmental interaction. The model includes a set of public services of a consumer nature with multichannel access and the use of “intelligent agents”. Thirdly, to what extent the subjects of government, acting on behalf of the state, use the provided opportunities. It is concluded that modern official documents regulating the processes of building a digital state do not consider digitalization as a mechanism that ensures the humanization and democratization of relations between government and society. Fourthly, discussing the presence of subjects of government acting on behalf of citizens, the author emphasized that the state has provided for the availability of a barrier-free information environment that provides high-quality public, medical and social services, but the issue of citizens as subjects of governance in digitalization processes is not provided. They act as clients and a source of information. The signs of the subject of management among citizens in modern management practice are revealed in terms of the possibilities of expressing their position, recognizing the need for joint actions in collecting critical information and exercising control over the implementation of decisions, the presence of some partnership in the interaction of authorities with the public. It is shown that these processes are at the beginning of their development today, the underdevelopment of services for public participation in managerial decision-making processes is emphasized, while the results of the digitalization are disputable and contradictory both at the theoretical and practical levels.